Hydrophobic lignin/polyurethane composite foam: An eco-friendly and easily reusable oil sorbent. (15th February 2022) - Hwang, Uiseok; Lee, Bumhee; Oh, Byeonghun; Shin, Hyun Su; Lee, Su Sam; Kang, Sang Gu; Kim, Donghee; Park, Jungwoo; Shin, Sunghee; Suhr, Jonghwan; Kim, Sung-Hoon; Nam, Jae-Do
Graphical abstract: Highlights: Lignin is acetylated to increase both compatibility with polymer matrix and hydrophobicity. The lignin-based composite foam is cheap, eco-friendly, and very easy to reuse. The absorption capacity of the sorbent foam is maintained for 50 cycles. Abstract: Global oil spill and water contamination issues are urgently requiring the development of next-generation oil sorbent materials that may desirably have the functionalities of reusability and biodegradability without generating secondary pollutions. Herein, a novel oil sorbent is introduced that could be practically useful in the cleanup for oils from contaminated water with low-cost and sustainability. The oil sorbent is composed of a polyurethane (PU) foam incorporated with hydrophobized lignin particles up to 40 wt%, in which the lignin is acetylated to increase the compatibility with the matrix and sorption capacity; for crude oil, the composite foam with an acetylated lignin content of 20 wt% shows increased absorption capacity of 8.06 g/g compared to the neat PU foam capacity of 4.51 g/g. The absorbed oil can be easily reclaimed simply by squeezing the foam with a good recyclability, which is maintained 97.9% and 92.3% of the mass-based sorption capacity even after 50 cycles for olive oil and crude oil, respectively. The developed composite foams and the methodology have enormous potential as a promising solution for the cleanup of organic contaminants.